Juger en homme(s) - Nicolas Picard (Clio@Themis)
If some works have studied the gender representations of judges on litigants, representations regarding members of the jury are less known. This paper intends to look at the moral and civic values required of them, in connection with their masculinity, at a time when only men were considered citizens. Members of the jury couldn’t show any weakness in their manly duty. Indeed, virility was then linked with firmness, rationality, composure and the rejection of sentimentality.